Cover Image, Volume 86, Issue 4. (April 2017) - Münzker, J.; Lindheim, L.; Adaway, J.; Trummer, C.; Lerchbaum, E.; Pieber, T.R.; Keevil, B.; Obermayer‐Pietsch, B.
Abstract : The cover image, by J. Münzker et al., is based on the Original article "High salivary testosterone‐to‐androstenedione ratio and adverse metabolic phenotypes in women with polycystic ovary syndrome, " DOI:10.1111/cen.13299